Longevity of Californian thistle roots - Bourd?t, G.W.; Leathwick, D.M.; Hurrell, G.A. (New Zealand Plant Protection, 2000)
In two experiments sheep pastures supporting manipulated ranges of root biomass of Californian thistle (Cirsium arvense (L) Scop) in autumn 1996 and 1997 were mown weekly over the subsequent growing seasons of 1997 and 1998 respectively This treatment minimised whole season photosynthetic opportunity in the Californian thistle and the formation of new root biomass allowing the survival of existing root biomass to be measured Autumnal root biomass in May 1997 was 6 of that in May 1996 and in May 1998 it was 10 of that in May 1997 These results support the hypothesis that a high percentage of the overwintering storage root biomass of Californian thistle does not survive beyond the end of the next growing season